Die Papyri Herkulaneums im Digitalen Zeitalter Neue Texte durch neue Techniken - eine Kurzeinführung - Fleischer, Kilian (Hans-Lietzmann-Vorlesungen, 2021)
The Herculaneum Papyri comprise the only surviving library of antiquity. In recent years, innovative technologies and new philological methods have effectively revolutionized research. Characters that were previously invisible are now emerging, and it will soon be possible to unroll complete rolls virtually. This book provides the first German introduction to the Herculaneum papyri and the potential of new imaging methods.